Pre-Treatment Physical Activity Could Positively Influence Pregnancy Rates in IVF despite the Induced Oxidative Stress: A Cohort Study on Salivary 8-Hydroxy-2'-deoxyguanosine - Viktória Prémusz; Dominika Lendvai-Emmert; Alexandra Makai; Krisztina Amrein; Shalini Chauhan; József Bódis; Kálmán András Kovács; Ákos Várnagy (MDPI AG, 2022)
(1) Background: This study was designed to define whether pretreatment habitual physical activity (PA)-induced oxidative stress (OS) influences outcome measures by using 8-hydroxy-2'-deoxyguanosine (8-OHdG) in saliva samples of patients undergoing in vitro fertilization (IVF). (2) Method: In this cohort study, samples were obtained from 26 patients (age: 34.6 ± 5.5 years, BMI: 25.3 ± 5.1, infertility: 51.0 ± 28.7 months) before the treatment and a follow-up of outcome measures of IVF/ICSI. The 8-OHdG was evaluated by Abcam's ELISA (ab201734), PA patterns by GPAQ-H and ActiGraph GT3X; (3) Results: The number of matured oocytes was positively influenced by the GPAQ-H recreation MET (R2 = 0.367, F = 10.994, p = 0.004; β = 0.005, p = 0.004, B Constant = 4.604) and a positive significant relationship (R2 = 0.757, F = 17.692, p < 0.001, B Constant = 1.342) was found with GPAQ-H recreational PA MET (β = 0.004, p < 0.001), and Grade 1 embryos and higher very vigorous activity (GT3X) were accompanied (R2 = 0.958, F = 408.479, p < 0.001) by higher ß-hCG levels (β = 63.703, p ≤ 0.001). Unanticipated positive correlation between 8-OHdG and ß-hCG level (R = 0.467, p = 0.028) was noticed, and there were significant differences in 8-OHdG in biochemical pregnancies (pregnant: 54.82 ± 35.56 ng/mL, non-pregnant: 30.06 ± 10.40 ng/mL, p = 0.022) as well. (4) Conclusions: Pretreatment PA could positively influence reproductive performance in IVF/ICSI despite the induced OS. However, a more sensitive biomarker and the recommended amount of activity should be further investigated.